Effect of Some Environmental Conditions on Durability of Clayey Soil Stabilized by Waste Lime - M. Al-Kiki, Ibrahaim (Anbar Journal of Engineering Sciences, 2012)
This investigation was conducted to assess the efficacy of some environmental conditions of soil specimens stabilized with optimum waste lime content 6%. These conditions are represented by cycles of (wetting-drying-freezing), (wetting-freezing-drying), (drying-wetting-freezing), (drying-freezing-wetting), (freezing-wetting-drying) and (freezing-drying-wetting). The soil specimens were subjected to these conditions, the durability of these specimens is study by knowledge the change in unconfined compressive strength, volume change and loss in weight. The results indicated that the unconfined compressive strength decreases with cycles for all conditions, but for different percentages according to the type condition. Where the condition more effect that starting freezing-drying-wetting. Also the results show that the specimens subjected to cycles of (freezing-drying-wetting) and (wetting-freezing-drying) destroyed at the end of eight cycle, but the specimens were subjected to other conditions destroyed at the end of tenth cycle. The results show that the maximum loss in weight for specimens subjected to cycles starting wetting-freezing-drying, and the maximum value of volume change for cycles starting freezing-drying-wetting. Finally these condition are regarded very severe conditions and effect on durability of soil stabilized.